ESTIMATION OF CBM RESOURCES IN TARAKAN SUB-BASIN - GANI (NIM : 220093060; Pembimbing : Dr. Ir. Dardji Noeradi, MUTIARA
Tarakan Basin in East Kalimantan is one of the Tertiary basins with an amount of coal. The coal seams in the study area were found in the Tabul and Santul Formation and were deposited in Miocene – Pliocene deltaic environment. This study aimed the potential of coal bed methane contained in the study area. And to achieve this purpose, at the early stage of this study, coal identification in the existing wells was conducted using cutting and wireline log analyses. Then, a 3D coal distribution model was created based on wells data and depth structure map from seismic data. Coal volume calculation was performed based on coal distribution model in the 300 m – 1200 m of depth, since the methane gas in the coal seams is formed optimally in this range of depth. Coal proximate data was obtained from the existing published literature and internal report of the company that occupied the study area. Kim formula was utilized to identify the coal bed methane contained in study area considering coal proximate analysis result, then the result of calculation from Kim formula was multiplied by coal volume from modeling process to acquire the volume of gas in place. The result showed the coal volume in the study area reaches 123x106 acre feet and the methane gas volume reaches 18,8 Tcf.